PENGARUH PENGGUNAAN MEDIA SOSIAL, MOTIVASI INTRINSIK, DAN PENDIDIKAN EKONOMI DALAM KELUARGA TERHADAP MINAT BERWIRAUSAHA ONLINE MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET - Wijaya, Riko Bangkit; Dewi Kusuma Wardani; Dini Octoria (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This research aims to determine the influence of social media usage, intrinsic motivation, and family economic education on students' interest in online entrepreneurship The study uses a quantitative descriptive method The population of this research is students from the Faculty of Education and Teacher Training at Universitas Sebelas Maret Surakarta, class of 2020-2022 The sampling technique used is simple random sampling with 373 respondents Data collection is done through a questionnaire using a Likert scale distributed via Google Form The data analysis used is multiple regression analysis using SPSS 26 software The research results conclude that there is a positive and significant influence of social media usage, intrinsic motivation, and family economic education together on students' interest in online entrepreneurship